L’aqueduc de Fontanières : un cinquième aqueduc romain à Lyon ? - Jean-Yves Barbier (Gallia)
In France, the Fourvière promontory, the original founding site of the Roman colony of Lyon/Lugdunum (Metropolis of Lyon), extends southwards into the line of hills that was left behind by the Alpine glaciers of the Lyon plateau, marking the steep eastern edge of the Massif Central at its point of contact with the Rhone Graben and river valley. Within this transitional zone, the steep hillside at the foot of which flows the Saône, downstream from and at its confluence with the Rhône in Antiquity, extends from west to east between the communes of Sainte-Foy-lès-Lyon (Metropolis of Lyon) and La Mulatière (Metropolis of Lyon) around a north-south road built into a ledge that follows, mid-slope, the direction of the Narbonne road that provided access to Lugdunum from the south. Facing east, this steep slope is known as the Balme de Fontanières and, thanks to the complex history of its geological formation, it offers abundant water resources, as evidenced by the resurgences and catchments from various periods in the vicinity of the eponymous road.The Romans could neither have ignored nor neglected the availability of these nearby resources, especially as to the north and west of the town, they had been forced to develop the remarkable network of four aqueducts spanning over 200 km long –including those of the Gier, Mont d’Or, Yzeron and Brévenne rivers– which captured the attention of renowned researchers such as G. M. Delorme, F. Artaud and C. Germain de Montauzan and, more recently, the leading experts on the “Four Lyon aqueducts,” a working group led by the Archéologie et Archéométrie (ArAr) laboratory. An examination of ancient references demonstrates that the remains of an aqueduct were known to exist in the Balme de Fontanières, but that they were too imprecise or had been misinterpreted and thus remained nearly entirely ignored throughout the 20th century.Curiously forgotten, F. Gabut’s description of a section of buried canal uncovered in the second half of the 19th century during groundworks for the construction of a house recently reappeared in a cultural heritage guidebook, thus re-launching the survey that would allow for the successive description of three remains found in situ. As a result of these investigations, it is now possible to confirm the existence of a fifth aqueduct at Fontanières, as well as to partially reconstruct its route over a distance of almost 1.50 km. It could have drawn water from hillside springs, such as those along the Fournache slopes below the town of Sainte-Foy, and collected it through the Balme cave in a buried canal, whose cross-section measures just 0.43 m less wide than that of the Mont d’Or aqueduct, though their configuration is otherwise quite similar, except for its covering, which was not found in the case of Fontanières. Its dimensions are comparable to those of certain sections of the Yzeron aqueduct. At La Mulatière, a well-preserved 19 m section of the canal is still visible within the Cave de la Fleurie, and 500 m further north, portions of its foundation were found in the Fontanières gardens, in proximity to numerous reused blocks of tile mortar that reveal the destruction of the pipe it was intended to support.Finally, diligent and unrelenting research, combining fortuitous location scouting and field surveys, tenacious consultation of archives and exploitation of a network of local contacts, led to the discovery, 1 km further north, in Lyon’s 5th arrondissement, of another section of the canal, over 18 m long, as far as the scree filling in its extension in the heights of the Montée Saint-Laurent, downstream from the Rue des Trois-Artichauts towards Choulans. A rigorous altimetric approach confirms, as F. Gabut had already rightly observed at the end of the 19th century, that the water would indeed have flowed from south to north towards Lyon/Lugdunum, rendering obsolete prior interpretations of an extension of the Brévenne aqueduct from its arrival at Saint-Irénée towards the south-east. At mid-slope, downstream from the Narbonne road, at an estimated invert elevation of 223 m, the canal had to negotiate the contours of the steep terrain of the Balme de Fontanières, without resorting to the aerial installations required by its four large and prestigious counterparts supplying the city’s highest districts from the west. It couldn’t compete with them, but it was an aqueduct that used the nearby resources provided by the groundwater of the Lyonnais plateau and the outlets on its eastern slopes. Indeed, this aqueduct was able to supply the intermediary levels of the Fourvière hill on the right bank of the Saône, as well as the sites (villae, craft or port facilities, sanctuaries, fountains or thermae) located below, and as far as the banks where the Rhône and Saône rivers converged. Many hypotheses have been put forward about its source, profile, destination and dating, but only the discovery of new elements will allow us to draw further conclusions.